Morphology of larval stages of Arrenurus cuspidator (O. F. Müller) and A. maculator (O. F. Müller) (Acari: Hydrachnidia) - Zawal, Andrzej (Zootaxa, 2006)
The morphology o f the larval stage of A. c uspidator is re-described and A. maculato r is described. Particular attention is paid to character differences between the two species. The present description of larval A. cuspidator is more deta iled than the previously published description. Larva e of both species ar e very simila r and di ffer only in four well de fined cha r acte r s: presence o f a hair b r ush on the base of the C1 seta in A. m aculato r ; the distance s Mp2-Mp2 , Mp1-Lp2 , C1-C2, C1 -CpI medial margin , and C4-CpIII medial ma rgin; th e length of the PV8 seta (longer in A. maculato r ); and the length of the antero-latera l indents in th e dorsa l plate (longer i n A. c uspidato r ). The species are separated from one another mainl y by the shape of dorsal plate with th e relatively deep anterolateral indents into which they cut at a straight ang le.